Konflik Kepentingan dan Budaya Populer di Masyarakat - Indah Yani; Irma Yusriani Simamora (Universitas Muhammadiyah Enrekang, 2022)
Conflict is something that cannot be avoided in life, especially in social life. In society, lifestyle is often influenced by what people read, see, so that whatever they feel they will do or follow. So that not a little western culture mushroomed among the people of Indonesia. The culture that is often followed by the community is called popular culture, yes it is a new thing and is being liked by many people. But it's not uncommon for popular culture to have its own conflicts, where the culture often violates the ethics that exist in our country, Indonesia, such as the rise of LGBT films which of course are very common and inappropriate to watch, or the proliferation of fast food that is being loved. The real muna is not good for health. There is only a small amount contained in the abstract because the discussion is so complex about